Factors related to adverse events from medicines in children hospitalized in a health institution in Sucre 2014-2018 - Martínez Reyes, Cielo (2019)
Objective. To determine the factors related to adverse drug events in children hospitalized in a health institution in Sucre-Colombia. Material and methods. Observational, descriptive, retrospective and relational study, in which 20 children were analyzed who had 23 Adverse Events for Drugs between January 2014 and June 2018. Results. 45% of the children were under one year of age and 91.3% were polyimedicalized. The most frequent EAM was the chemical phlebitis with 34.78%. 91.30% were preventable, because they were a consequence of human failures such as error in the prescription (13.04%), dispensation (13.04%), application of the wrong medication (30.43%), incorrect dilution (13.04) %), the permeability of the venous access was not verified (8.7%) and 17.3% were EAM tracers, that is, mistakes were made in several phases of the process. 43.47% occurred at night. There was a sentinel EAM and 65.22% were mild. There was no evidence of nursing follow-up after the EAM in 65.22% of the cases. There was a statistical relationship between prolongation of stay (p = 0.018), prescription (p = 0.018), nursing errors (p = 0.0023) and anatomical site affected (p = 0.001) with the occurrence of them EAM. Conclusions. EAMs are always present, because they are implicit in care; the prevention depends on the institutional commitment of the professionals before the correct fulfillment of their work and of involving the caregivers and the patient in their safety.